2012
DOI: 10.1007/s12192-011-0305-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of alopecia areata with quercetin in the C3H/HeJ mouse model

Abstract: Alopecia areata (AA) is an autoimmune nonscarring hair loss disorder. AA can be acute, recurrent, or chronic. Current therapeutic options for AA are limited, and there is no effective prevention for recurrent AA. We have previously shown a correlation between the expression of HSP70 (HSPA1A/B), a heat shock protein involved in the inflammatory response, and the onset of AA in the C3H/ HeJ mouse model. In this study, we tested the effects of quercetin, a bioflavonoid with anti-inflammatory properties, on AA dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
1
24
0
2
Order By: Relevance
“…As a remedy for vitiligo, quercetin has potential to enhance melanogenesis on human epidermis by affecting on maturation of melanosomes [39] and increase the activity and biosynthesis of tyrosinase in melanoma cells and in human melanocytes [40]. Regarding to hair growth, this compound was reported to treat and prevent of alopecia areata [41] and inhibit of 5 α-reductase [42]. …”
Section: Resultsmentioning
confidence: 99%
“…As a remedy for vitiligo, quercetin has potential to enhance melanogenesis on human epidermis by affecting on maturation of melanosomes [39] and increase the activity and biosynthesis of tyrosinase in melanoma cells and in human melanocytes [40]. Regarding to hair growth, this compound was reported to treat and prevent of alopecia areata [41] and inhibit of 5 α-reductase [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Another plant with similar effects is Ginko biloba (GBE). This plant is rich in Quercetin, a bioflavonoid with anti‐inflammatory properties . Mice with spontaneous AA were treated with subcutaneous quercetin or sham injections.…”
Section: Methodsmentioning
confidence: 99%
“…Mice with spontaneous AA were treated with subcutaneous quercetin or sham injections. Hair regrowth was observed in lesional areas in all the quercetin‐treated mice . Effects of 70% ethanolic extract from leaves of GBE on the hair regrowth in normal and high butter diet‐pretreated C3H strain mice which posterior hair we shaved were investigated .…”
Section: Methodsmentioning
confidence: 99%
“…According to Perez-Vizcanio et al [7], quercetine, a flavonoid-type compound, can act as a vasodilator. Furthermore, in correlation to alopecia aerate, there was a study found that the administration of 10 µM quercetin subcutaneously may help the condition [8].…”
Section: Introductionmentioning
confidence: 99%